Development of an Open-Source 3D-Printed Material Synthesis Robot FLUID: Hardware and Software Blueprints for Accessible Automation in Materials Science - Kuwahara, Mikael; Hasukawa, Yoshiki; Garcia-Escobar, Fernando; Maeda, Satoshi; Takahashi, Lauren; Takahashi, Keisuke (ACS applied engineering materials, 2025)
The automation of materials design has emerged as a key focus in the field of materials science. The advent of materials informatics marked an important step toward this goal, utilizing data-driven approaches to accelerate the discovery and optimization of materials. However, the adoption of robotic systems for automated synthesis has been relatively gradual, influenced by the technical challenges and complexity of implementation. Here, the development of FLUID, an open-source, 3D-printed robotic platform for material synthesis, is presented. FLUID provides a comprehensive blueprint for both hardware and software, enabling accessible and customizable automation for a broad range of researchers. The system’s performance is experimentally validated through the materials synthesis, demonstrating its capability and flexibility. This approach aims to democratize automation in material synthesis, providing researchers with a practical, cost-effective solution to accelerate innovation in materials science.